Chemotherapy and healthcare utilisation near the end of life in patients with cancer. (16th November 2017) - Schulkes, K.J.G.; van Walree, I.C.; van Elden, L.J.R.; van den Bos, F.; van Huis‐Tanja, L.; Lammers, J.‐W.J.; ten Bokkel Huinink, D.; Hamaker, M.E.
Abstract : The quality of medical care delivered to patients with cancer near the end of life is a significant issue. Previous studies have defined several areas suggestive of aggressive cancer treatment as potentially representing poor quality care. The primary objective of current analysis was to examine chemotherapy and healthcare utilisation in the last 3 months of life among patients with cancer that received palliative chemotherapy. Patients were selected from the hospital administration database of the Diakonessenhuis Utrecht, the Netherlands. Data were extracted from the medical files. A total of 604 patients were included for analysis (median age: 64 years). For 300 patients (50%) chemotherapy was given in the last 3 months (CT+). For 76% ( n = 229) of CT+ patients unplanned hospital admissions were made in these last 3 months, compared to 44% ( n = 133) of CT− patients ( p < .001). Visits to the emergency room in last 3 months were made by 67% ( n = 202) of CT+ patients compared to 43% ( n = 132) of CT− patients ( p < .001). Healthcare consumption was significantly higher in patients who received chemotherapy in the last 3 months of life. Being able to inform our patients about these aspects of treatment can help to optimise both the quality of life and the quality of dying in patients with cancer.